New State Capital Policy in the Context of Equitable Development in Indonesia - Zamani, Muhammad Bagus; Saputro, Muhammad Noor Cahyadi Eko; Mutiarin, Dyah (Prosiding University Research Colloquium, 2023)
A capital is a city that is considered the seat of government of a country or region. The capital is often seen as a symbol of the state and is the residence for the president or state leaders. The capital is also often the most important city from a political, economic and cultural point of view. In some cases, the capital is also the most popular and densely populated city. However, in some countries, the capital may be changed or moved to another city. Moving the Indonesian capital from Jakarta to Kalimantan is a decision taken by the Indonesian government to move the nation’s capital from Jakarta to another region, namely Kalimantan. This move was made with the aim of reducing pressure on Jakarta which is currently experiencing environmental problems and severe traffic jams, as well as to spread development to other areas of the country. The relocation of the capital will result in major changes for the people of Indonesia, including changes in economic, social and cultural terms.